Are you the One who is to come?: the historical Jesus and the messianic question - Bird, Michael (Baker Academic, 2009)
"Jesus who is called the Christ" -- Messianic expectations in Second Temple Judaism -- Messiah Jesus : a role declined -- MessiahJesus : a role redefined -- Messiah Jesus : a crucified Messiah -- Toward a messianic christology